Improvement in Touch Sensation after Stroke is Associated with Resting Functional Connectivity Changes - Bannister, Louise C.; Crewther, Sheila G.; Gavrilescu, Maria; Carey, Leeanne M. (Frontiers in Neurology, 2015)
Background: Distributed brain networks are known to be involved in facilitating behavioural improvement after stroke, yet few, if any, studies have investigated the relationship between improved touch sensation after stroke and changes in functional brain connectivity. Objective: We aimed to identify how recovery of somatosensory function in the first six months after stroke was associated with functional network changes as measured using resting-state connectivity analysis of functional magnetic resonance imaging (fMRI) data. Methods: Ten stroke survivors underwent clinical testing and resting-state fMRI (rsfMRI) scans at one and six months post-stroke. Ten age-matched healthy participants were included as controls. Results: Patients demonstrated a wide range of severity of touch impairment one month post-stroke, followed by variable improvement over time. In the stroke group, significantly stronger interhemispheric functional correlations between regions of the somatosensory system, and with visual and frontal areas, were found at six months than at one month post-stroke. Clinical improvement in tactile discrimination was associated with stronger correlations at six months between contralesional secondary somatosensory cortex (SII) and inferior parietal cortex (IPC) and middle temporal gyrus, and between contralesional thalamus and cerebellum. Conclusions: The strength of connectivity between somatosensory regions and distributed brain networks, including vision and attention networks, may change over time in stroke survivors with impaired touch discrimination. Connectivity changes from contralesional SII and contralesional thalamus are associated with improved touch sensation at 6-months post-stroke. These functional connectivity changes could represent future targets for therapy.